Proteomic snapshot of the EGF‐induced ubiquitin network - Argenzio, Elisabetta; Bange, Tanja; Oldrini, Barbara; Bianchi, Fabrizio; Peesari, Raghunath; Mari, Sara; Di Fiore, Pier Paolo; Mann, Matthias; Polo, Simona (Molecular systems biology, 2011)
The activity, localization and fate of many cellular proteins are regulated through ubiquitination, a process whereby one or more ubiquitin (Ub) monomers or chains are covalently attached to target proteins. While Ub‐conjugated and Ub‐associated proteomes have been described, we lack a high‐resolution picture of the dynamics of ubiquitination in response to signaling. In this study, we describe the epidermal growth factor (EGF)‐regulated Ubiproteome, as obtained by two complementary purification strategies coupled to quantitative proteomics. Our results unveil the complex impact of growth factor signaling on Ub‐based intracellular networks to levels that extend well beyond what might have been expected. In addition to endocytic proteins, the EGF‐regulated Ubiproteome includes a large number of signaling proteins, ubiquitinating and deubiquitinating enzymes, transporters and proteins involved in translation and transcription. The Ub‐based signaling network appears to intersect both housekeeping and regulatory circuitries of cellular physiology. Finally, as proof of principle of the biological relevance of the EGF‐Ubiproteome, we demonstrated that EphA2 is a novel, downstream ubiquitinated target of epidermal growth factor receptor (EGFR), critically involved in EGFR biological responses. In this work, the authors report the first proteome‐wide analysis of EGF‐regulated ubiquitination, revealing surprisingly pervasive growth factor‐induced ubiquitination across a broad range of cellular systems and signaling pathways. Synopsis In this work, the authors report the first proteome‐wide analysis of EGF‐regulated ubiquitination, revealing surprisingly pervasive growth factor‐induced ubiquitination across a broad range of cellular systems and signaling pathways. Ubiquitination is a process by which one or more ubiquitin (Ub) monomers or chains are covalently attached to target proteins by E3 ligases. Deubiquitinating enzymes (DUBs) revert Ub conjugation, thus ensuring a dynamic equilibrium between pools of ubiquitinated and deubiquitinated proteins (Amerik and Hochstrasser, 2004 ). Traditionally, ubiquitination has been associated with protein degradation; however, it is now becoming apparent that this post‐translation modification is an important signaling mechanism that can modulate the function, localization and protein/protein interaction abilities of targets (Mukhopadhyay and Riezman, 2007 ; Ravid and Hochstrasser, 2008 ). One of the best‐characterized signaling pathways involving ubiquitination is the epidermal growth factor (EGF)‐induced pathway. Upon EGF stimulation, a variety of proteins are subject to Ub modification. These include the EGF receptor (EGFR), which undergoes both multiple monoubiquitination (Haglund et al , 2003 ) and K63‐linked polyubiquitination (Huang et al , 2006 ), as well as components of the downstream endocytic machinery, which are modified by monoubiquitination (Polo et al , 2002 ; Mukhopadhyay and Riezman, 2007 ). Ubiquitination of the EGFR has been shown to have an impact on receptor internalization, intracellular sorting and metabolic fate (Acconcia et al , 2009 ). However, little is known about the wider impact of EGF‐induced ubiquitination on cellular homeostasis and on the pleiotropic biological functions of the EGFR. In this paper, we attempt to address this issue by characterizing the repertoire of proteins that are ubiquitinated upon EGF stimulation, i.e., the EGF‐Ubiproteome. To achieve this, we employed two different purification procedures (endogenous—based on the purification of proteins modified by endogenous Ub from human cells; tandem affinity purification (TAP)—based on the purification of proteins modified by an ectopically expressed tagged‐Ub from mouse cells) with stable isotope labeling with amino acids in cell culture‐based MS to obtain both steady‐state Ubiproteomes and EGF‐induced Ubiproteomes. The steady‐state Ubiproteomes consist of 1175 and 582 unambiguously identified proteins for the endogenous and TAP approaches, respectively, which we largely validated. Approximately 15% of the steady‐state Ubiproteome was EGF‐regulated at 10 min after stimulation; 176 of 1175 in the endogenous approach and 105 of 582 in the TAP approach. Both hyper‐ and hypoubiquitinated proteins were detected, indicating that EGFR‐mediated signaling can modulate the ubiquitin network in both directions. Interestingly, many E2, E3 and DUBs were present in the EGF‐Ubiproteome, suggesting that the Ub signal might be rapidly transmitted and amplified through the Ub machinery. Moreover, analysis of Ub‐chain topology, performed using mass spectrometry and specific abs, suggested that the K63‐linkage was the major Ub‐based signal in the EGF‐induced pathway. To obtain a higher‐resolution molecular picture of the EGF‐regulated Ub network, we performed a network analysis on the non‐redundant EGF‐Ubiproteome (265 proteins). This analysis revealed that in addition to well‐established liaisons with endocytosis‐related pathways, the EGF‐Ubiproteome intersects many circuitries of intracellular signaling involved in, e.g., DNA damage checkpoint regulation, cell‐to‐cell adhesion mechanisms and actin remodeling (Figure 5A ). Moreover, the EGF‐Ubiproteome was enriched in hubs, proteins that can establish multiple protein/protein interaction and thereby regulate the organization of networks. These results are indicative of a crosstalk between EGFR‐activated pathways and other signaling pathways through the Ub‐network. As EGF binding to its receptor also triggers a series of phosphorylation events, we examined whether there was any overlap between our EGF‐Ubiproteome and published EGF‐induced phosphotyrosine (pY) proteomes (Blagoev et al , 2004 ; Oyama et al , 2009 ; Hammond et al , 2010 ). We observed a significant overlap between ubiquitinated and pY proteins: 23% (61 of 265) of the EGF‐Ubiproteome proteins were also tyrosine phosphorylated. Pathway analysis of these 61 Ub/pY‐containing proteins revealed a significant enrichment in endocytic and signal‐transduction pathways, while ‘hub analysis’ revealed that Ub/pY‐containing proteins are enriched in highly connected proteins to an even greater extent than Ub‐containing proteins alone. These data point to a complex interplay between the Ub and pY networks and suggest that the flow of information from the receptor to downstream signaling molecules is driven by two complementary and interlinked enzymatic cascades: kinases/phosphatases and E3 ligases/DUBs. Finally, we provided a proof of principle of the biological relevance of our EGF‐Ubiproteome. We focused on EphA2, a receptor tyrosine kinase, which is involved in development and is often overexpressed in cancer (Pasquale, 2008 ). We started from the observation that EphA2 is present in the EGF‐Ubiproteome and that proteins of the EGF‐Ubiproteome are enriched in the Ephrin receptor signaling pathway(s). We confirmed the MS data by demonstrating that the EphA2 is ubiquitinated upon EGF stimulation. Moreover, EphA2 also undergoes tyrosine phosphorylation, indicating crosstalk between the two receptors. The EGFR kinase domain was essential for these modifications of EphA2, and a partial co‐internalization with EGFR upon EGF activation was clearly detectable. Finally, we demonstrated by knockdown of EphA2 in MCF10A cells that this receptor is critically involved in EGFR biological outcomes, such as proliferation and migration (Figure 7 ). Overall, our results unveil the complex impact of growth factor signaling on Ub‐based intracellular networks to levels that extend well beyond what might have been expected and highlight the ‘resource’ feature of our EGF‐Ubiproteome. Epidermal growth factor (EGF) triggers a novel ubiquitin (Ub)‐based signaling cascade that appears to intersect both housekeeping and regulatory circuitries of cellular physiology. The EGF‐regulated Ubiproteome includes scores ubiquitinating and deubiquitinating enzymes, suggesting that the Ub signal might be rapidly transmitted and amplified through the Ub machinery. The EGF‐Ubiproteome overlaps significantly with the EGF‐phosphotyrosine proteome, pointing to a possible crosstalk between these two signaling mechanisms. The significant number of biological insights uncovered in our study (among which EphA2 as a novel, downstream ubiquitinated target of EGF receptor) illustrates the general relevance of such proteomic screens and calls for further analysis of the dynamics of the Ubiproteome.